Musealized landscapes and petrified landscapes - Stobiecka, Monika (Polskie Studia Krajobrazowe, 2020)
The text aims to reflect upon the notion of landscape in the context of exhibitions; more precisely, it aims to do so in relation to the musealization of archaeological heritage and presentation of archaeology. The last 30 years of museum transformations, referred to as “the age of museums,” and the digital shift in museology have had a significant impact on building archaeological narratives in museums and beyond. Immersive and telematic landscapes, currently being constructed in museums, allow for sensorial engagement, broadened perceptive possibilities, and more intense interest in archaeology with the use of complex and convincing visions of the past. Hence, the musealized landscape presented in this paper is to go beyond the traditional criticism of multimedia in museums; it is an attempt to appreciate the cognitive opportunities provided by modern archaeological exhibitions.